Food Unfiltered - Manogaran, Aravind (2018)
This paper presents Food Unfiltered, an educational campaign that aims to promote the consumption of ugly food. Led by four final-year undergraduates from the Wee Kim Wee School of Communication and Information at Nanyang Technological University, the campaign targets Singaporean grocery shoppers aged 20 to 59 years old. The campaign highlights the need to reduce food waste caused by cosmetic filtering — the discarding of perfectly-edible food that appears to be ugly or less than perfect according to personal or perceived market standards. This report presents the findings from primary and secondary research conducted by the team, which helped shape the campaign’s goal, objectives and strategies. The problems identified during the formative research include a lack of self-efficacy in differentiating ugly from spoilt food, negative attitudes towards ugly food and low behavioural intention to purchase and consume ugly food. Based on research, key messages and campaign strategies of “correcting misconceptions”, “reframing”, “use of ecotainment” and “strategic partnerships” were crafted. Subsequent sections detail the campaign’s progress from conceptualisation to execution, along with the program monitoring and changes made along the way. Lastly, the effectiveness of the campaign was evaluated, followed by a discussion on key achievements, plans for the continuation of the campaign and recommendations for future projects of similar nature. This report is accompanied by appendices containing campaign materials, including campaign collaterals, event photographs and relevant data as references to the main report.